A Glimpse on Bihars and Bahais in Lalitpur Town - Bajracharya, Kishor Bajra (The Third Pole: Journal of Geography Education, 2014)
This paper deals with the distribution Bihars and Bahais of Patan area of Lalitpur district. Bihars and Bahis are the places where Buddhist monks and nuns stay live and carry out different activities like praying, meditation, leering and studying. Available evidences prove that the Bihars and Bahis in Kathmandu valley were even during the lifetime of Shakyamuni Gautam Buddha. There are three types of Buddhist Bihars namely General Bihar, Madhyamik Bihar and Mahabihar. Altogether there are 167 Bihars of different period in Lalitpur town. Most of them have now been remained only in name and their condition is not good. Except few, all Bahis have been badly damaged in the absence of the regular care and maintenance. The situation might be more critical and worse if nothing is worked out to reconcile the problems. DOI: http://dx.doi.org/10.3126/ttp.v11i0.11556 The Third Pole Vol. 11-12, 2012 Page : 56-60